Raven Chacon - a worm's eye view from a bird's beak - Chacon, Raven 1977- (Sternberg Press, 2024)
"A career-spanning catalogue featuring excerpts from Raven Chacon's scores, musical prompts, and drawings interspersed with full-color documentation and descriptive texts of installations, sculptures, and performances. Raven Chacon is a composer and artist creating musical experiences that explore relationships among land, space, and people. In an experimental practice that cuts across the boundaries of visual art, performance, and music, Chacon breaks open musical traditions and activates spaces of performance where the histories of the lands the United States has encroached upon can be contemplated, questioned, and reimagined. In 2022, Raven Chacon became the first Native American to win the Pulitzer Prize for Music, and was awarded a prestigious MacArthur zgeniusy fellowship in 2023. This monograph gives readers an insight into how Chacon uses sound, video, scores, performance and sculpture to address urgent matters of Indigenous sovereignty and environmental justice." -- Publisher
Impressum: Published on the occasion of the exhibition "Raven Chacon: A Worm's Eye View from a Bird's Beak" at Swiss Institute, New York, January 25 - April 14, 2024; Nordnorsk Kunstmuseum, Northern Norway/Sápmi, March 16 - September 1, 2024
Keywords: Chacon, Raven -- 1977-; Chacon, Raven / Themes, motives / Exhibitions; Indigenous peoples / America; Indigenous art; Navajo art; Art, American / 20th century / Exhibitions; Art, American / 21st century / Exhibitions; Ausstellungskatalog -- Nordnorsk Kunstmuseum -- 16.03.2024-01.09.2024 -- Tromsø; Ausstellungskatalog -- Swiss Institute - Contemporary Art -- 25.01.2024-14.04.2024 -- New York, NY; Bildband